TINDAK TUTUR DIREKTIF DAN STRATEGI BERTUTUR DALAM BAHASA MINANGKABAU OLEH REMAJA ANTARKAWAN SEBAYA PADA KOMUNIKASI TIDAK RESMI DI KOTA PADANG - Fajri, Danty Awalliah; Manaf, Ngusman Abdul; Juita, Novia (Universitas Negeri Padang, 2017)
This article was written to describe (1) the type of speech acts directive used in Minangkabau language by peer-teenagers for non formal communication in Padang city, (2) the strategy of speaking used in Minangkabau language by peer-teenagers for non formal communication in Padang city, (3) the context of the speaking situation used for non formal communication in Minangkabau language by peer-teenagers in Padang city, and (4)Â the politeness way of speaking usedÂ by peer-teenagers in Minangkabau language for non formal communication in Padang city. The data was recorded conversation of peer-teenagers that consisted of 147 utterances in Padang city. The data sources came from young teenager in same age in non-formal communication in Padang. The data was taken by using the method of listening with the technique of tapping. The data was analyzed for describing and clarifying that based on the type of directive speech act, strategy in speaking and the context of the its situation, and the way of teenagersâ€™ speaking in politeness. The findings are, (1) the type of directive speech act is widely used in ordered and inquire speech act, (2) the speaking strategy which was widely used is the speaking frankly without preamble strategy, (3) the context consists of: the sensitive topics of the pleasantries positive politeness of speaking strategy and the not-sensitive topics tend to the speaking frankly without preamble strategy, and (4) the politeness tends to use the pleasantries positive politeness of speaking strategy.Keywords :speech act, strategy of speaking, non formal communication